The role of self-regulatory skills in sport and academic performances of elite youth athletes - Jonker, L.; Elferink-Gemser, M. T.; Visscher, C. (Talent Development & Excellence, 2011)
Success in sport and school is related to self-regulation. Additionally, sport experts are high academic achievers. We examined the role of 6 self-regulatory skills in the sport and academic performances of elite youth athletes (12-16 years) and compared their scores with age-matched controls in 2 academic secondary school systems (pre-university vs. pre-vocational). Pre-university students outscored pre-vocational students on 5 self-regulatory skills in the control group while 2 skills were significant in an athletes` population. When comparing elite athletes to controls within each academic system, 3 self-regulatory skills were significant. Moreover, pre-vocational athletes outscored pre-university controls on 1 skill. These results expand theories of transfer by suggesting that self-regulation may help elite youth athletes to combine a sport career with education.